2012
DOI: 10.1590/s1519-69842012000200010
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of a spinosyn's family insecticide on energy metabolism and liver morphology in frugivorous bats Artibeus lituratus (Olfers, 1818)

Abstract: A new class of insecticide derived from fermentation of Sacharopolyspora spinosa -spinosad, has been indicated as being of low toxicity and a natural alternative to classical pesticides. In order to elucidate several aspects related to the morphophysiological changes induced by spinosad in Artibeus lituratus, the effects of a seven-day administration on plasma glucose, glycogen, protein and lipid concentrations were evaluated, and possible changes in liver cells were examined by histological analysis. Animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…Papaya fruits were chosen due to their high acceptance from bats in captivity (Amaral et al . ,b). Fruits were dipped in one of the above‐mentioned solutions and left to dry in an adapted container to prevent contact and therefore losses of the insecticide in the outer layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Papaya fruits were chosen due to their high acceptance from bats in captivity (Amaral et al . ,b). Fruits were dipped in one of the above‐mentioned solutions and left to dry in an adapted container to prevent contact and therefore losses of the insecticide in the outer layer.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies from our laboratory showed histopathological alterations in the livers of fruit‐eating bats that have been exposed to environmentally relevant concentrations of the insecticide fenthion (Amaral et al . ,b). As the liver and kidneys are the main organs involved with metabolism and excretion of xenobiotics and their residual metabolic by‐products (Astiz et al .…”
mentioning
confidence: 99%
“…Na literatura recente, encontramos trabalhos que avaliaram o metabolismo energético e a mobilização das reservas metabólicas em morcegos no Brasil. No entanto, a maioria desses estudos foi realizada em região de Mata Atlântica (Barros et al, 2013;Amaral et al, 2012aAmaral et al, , 2012bMelo et al, 2012;Freitas et al, 2010) e, apenas Melo e colaboradores (2012) relacionaram as reservas energéticas à alteração do habitat.…”
Section: Efeito Da Fragmentação Sobre Morcegosunclassified
“…Neotropical são voltados a poucas espécies e habitats (Barros et al, 2013;Amaral et al, 2012aAmaral et al, , 2012bMelo et al, 2012;Freitas et al, 2010Freitas et al, , 2006Freitas et al, , 2003Pinheiro et al, 2006). A avaliação da resposta à alteração do ambiente fica limitada a comparação com outros tipos de ambiente.…”
Section: Estudos Que Avaliaram a Mobilização De Reservas Energéticas unclassified
See 1 more Smart Citation